2007
DOI: 10.4269/ajtmh.2007.77.627
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Treatment Efficacy among People Living with HIV: The Role of Host and Parasite Factors

Abstract: Identification of an effect of HIV-associated immunosuppression on response to antimalarial therapy would help guide management of malaria infection in areas of high HIV prevalence. Therefore, we conducted an observational study of people living with HIV infection in Blantyre, Malawi. Participants who developed malaria were treated with sulfadoxine-pyrimethamine (SP) and followed for 28 days. Molecular markers for SP resistance were measured. One hundred seventy-eight episodes of malaria were assessed. The 28-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…To the best of our knowledge this is the first time that delayed clearance of malaria parasites among children has been reported. Studies among HIV-infected adult populations have reported conflicting results depending on the malaria treatment regimen used and the CD4 count (Kamya et al, 2006; Laufer et al, 2007; Müller and Moser, 1990; Patnaik et al, 2005; Shah et al, 2006; Van Geertruyden et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the first time that delayed clearance of malaria parasites among children has been reported. Studies among HIV-infected adult populations have reported conflicting results depending on the malaria treatment regimen used and the CD4 count (Kamya et al, 2006; Laufer et al, 2007; Müller and Moser, 1990; Patnaik et al, 2005; Shah et al, 2006; Van Geertruyden et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…The increased severity of malaria symptoms probably occurs as a consequence of the falling of the CD4-cell count in HIVinfected individuals. Antimalarial treatment failure has also been shown to be more common in HIV-infected adults with low CD4-cell counts compared to then on HIV-infected individuals (Kamya et al, 2006;Shah et al, 2006;Laufer et al, 2007). However, there is unclear evidence of an increasing in the rates of severe or complicated malaria in HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 92%
“…For example, the ability to clear drug-resistant malaria in HIV-infected young children does not seem to correlate with CD4 level. 62 However, some studies suggest that HIV/malaria-coinfected children have higher rates of parasitemia and parasite density than children infected with malaria only. 62,63 Studies show HIV/malaria-coinfected children are also more likely to suffer comorbidities than HIV-uninfected children.…”
Section: Resultsmentioning
confidence: 99%
“…62 However, some studies suggest that HIV/malaria-coinfected children have higher rates of parasitemia and parasite density than children infected with malaria only. 62,63 Studies show HIV/malaria-coinfected children are also more likely to suffer comorbidities than HIV-uninfected children. They may also be more likely to develop anemia 64,65 or cerebral malaria.…”
Section: Resultsmentioning
confidence: 99%